Directionality of Person–Situation Transactions: Are There Spillovers Among and Between Situation Experiences And Personality States?. (July 2016) - Rauthmann, John F.; Jones, Ashley Bell; Sherman, Ryne A.
To elucidate temporal sequences among and between person and situation variables, this work examines cross-measurement spillovers between situation experiences S (on the Situational Eight DIAMONDS characteristics [Duty, Intellect, Adversity, Mating, pOsitivity, Negativity, Deception, Sociality]) and personality states P (on the Big Six HEXACO dimensions [Honesty/Humility, Emotionality, eXtraversion, Agreeableness, Conscientiousness, Openness to Experience]) in experience sampling data. Multi-level modeling of lagged data at tn -1 and non-lagged data at tn grants the opportunity to examine (a) the stability (P → P, S → S), (b) cross-sectional associations (S ↔ P), and (c) cross-lagged associations among and between situation experiences and personality states (S → P, P → S). Findings indicated that there were (a) moderate stability paths, (b) small to moderate cross-sectional paths, and (c) only very small cross-lagged paths (though the different situation characteristics and personality states showed differential tendencies toward no directionality, S → P or P → S unidirectionality, or bidirectionality). Findings are discussed in light of refining studies on dynamic person–situation transactions.